2018
DOI: 10.1039/c8ra01774c
|View full text |Cite
|
Sign up to set email alerts
|

Generation of micro- and nano-morphologies on a stainless steel surface irradiated with 257 nm femtosecond laser pulses

Abstract: a Surface structuring by femtosecond lasers has emerged as an efficient tool to functionalize the surfaces of various solid materials. Laser induced periodic surface structures (LIPSS) can drastically impact the wetting, friction and optical properties of the surface depending on the size, aspect ratio and period of the structures. Morphological characteristics in the nanoscale, such as nano roughness, contributing to a hierarchical surface formation are considered to have a significant impact on those propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
(60 reference statements)
1
18
0
2
Order By: Relevance
“…12(b). Between the LSFL crests, smaller structures are formed parallel to laser polarization with periods ≈ 200 nm, resembling crossoriented HSFL commonly observed in experiments [21,22,43,59,68,69]. We note that the energy is absorbed in the hollows of the LSFL structures mostly perpendicular to laser polarization, amplifying the pre-existent gratings.…”
Section: Multipulse Simulationssupporting
confidence: 72%
See 2 more Smart Citations
“…12(b). Between the LSFL crests, smaller structures are formed parallel to laser polarization with periods ≈ 200 nm, resembling crossoriented HSFL commonly observed in experiments [21,22,43,59,68,69]. We note that the energy is absorbed in the hollows of the LSFL structures mostly perpendicular to laser polarization, amplifying the pre-existent gratings.…”
Section: Multipulse Simulationssupporting
confidence: 72%
“…The formation of microstructures such as grooves and spikes was then explained by Tsibidis et al based on the solution of incompressible Navier-Stokes equations, indicating the generation of hydrothermal waves and convection rolls for low and high Prandtl number fluids accordingly due to thermal gradients created by previously formed LSFL [39,40]. Nevertheless, the existing models fail to explain the formation of regular HSFL with orientations both perpendicular and parallel to laser polarization and periods down to λ/15 on metal surfaces [22,43], as well as more complex morphologies, consisting of hierarchical periodic surface structures [19,21,22,43,59,60,[67][68][69] and quasihexagonal arrangements [36, 47, 49-53, 70, 71]. For instance, the transitions between HSFL and LSFL are contradictory discussed in the literature, where both lithographic scenarios, based on electromagnetic field enhancement between regular rectangu-lar grooves and period reduction or grating splitting [57,[72][73][74][75], and hydrodynamic scenarios based on the instability [48,59,60] were proposed.…”
Section: Overview Of Self-organized Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, lots of research activities have been reported on LIPSS, which represent a versatile and practical way to functionalize the surface of metals [ 9 , 10 , 11 , 12 , 13 ], dielectrics [ 14 , 15 , 16 ] and semiconductors [ 17 , 18 , 19 ]. Current applications of LIPSS span from the control of surface wetting to the tailoring of surface colonization by bacterial biofilms, from the improvement of the tribological performance of nanostructured metal surfaces to the efficient water-oil separation in marine oil spills [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Наносекундные импульсы УФ-лазера способны модифицировать поверхность металла, существенно изменяя его поверхностные свойства [1][2][3][4]. Диффузионная сварка металлов, обработанных подобным образом, заметно улучшается благодаря интенсификации диффузионных процессов в зоне контакта соединяемых поверхностей [5].…”
unclassified